2011
DOI: 10.1149/1.3591045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Bismuth Sulfide/Silicon Junction for Building Thin Film Solar Cells

Abstract: Feasibility of combining p-type crystalline Si (c-Si) of 200–8000 nm in thickness with an n-type bismuth sulfide (Bi2S3) thin film of 300 nm in thickness for thin film solar cell is analyzed. Theoretical analysis shows that the high optical absorption coefficient (105 cm−1) of Bi2S3 results in a light-generated current density (JL ) of >20 mA/cm2 for a c-Si(200 nm)/Bi2S3(300 nm) stack at a combined film thickness of 500 nm, and with an open circuit voltage (Voc ) of nearly 600 mV. Proof-of-concept cell structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 62 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…Determined band gaps reach from 1.2 to 2.0 eV and absorption coefficients of αfalse(ωfalse)>105cm −1 in the visible region have been identified . So far, Bi2S3 solar cells with either PbS or c‐Si () as p‐type layer lack efficiencies and have a rather low open‐circuit voltage Voc<500meV compared to the band gap, indicating a loss of conversion efficiency either due to recombination via defects in the Bi2S3 bulk or at the interfaces in the solar cell. It has been shown that Bi2S3 can aggregate to nanowires, rods, flakes and flower‐like formations of stoichiometric Bi2S3 and that the occurrence and shape depends on the substrate temperature during deposition, the deposition method or the layer thickness .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determined band gaps reach from 1.2 to 2.0 eV and absorption coefficients of αfalse(ωfalse)>105cm −1 in the visible region have been identified . So far, Bi2S3 solar cells with either PbS or c‐Si () as p‐type layer lack efficiencies and have a rather low open‐circuit voltage Voc<500meV compared to the band gap, indicating a loss of conversion efficiency either due to recombination via defects in the Bi2S3 bulk or at the interfaces in the solar cell. It has been shown that Bi2S3 can aggregate to nanowires, rods, flakes and flower‐like formations of stoichiometric Bi2S3 and that the occurrence and shape depends on the substrate temperature during deposition, the deposition method or the layer thickness .…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth sulfide (Bi2S3) is a non‐toxic V–VI binary n‐type semiconductor and considered as a potential candidate for thin film solar cells . Determined band gaps reach from 1.2 to 2.0 eV and absorption coefficients of αfalse(ωfalse)>105cm −1 in the visible region have been identified .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] In a thin film of 40 nm in thickness produced by thermal evaporation on unheated substrates, it is 2.8 eV. [ 11 ] In these cases, the films appear yellowish in transmitted daylight. Through crystalline thin films of the materials of the same thickness, the color is brownish‐red.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different studies on Bi 2 S 3-based solar cells, many reports are on the thin film-based solar cells (Wang et al 2007;Moreno-García et al 2011;Becerra et al 2011) and photoelectrochemical solar cells (PEC) (Bhattacharya and Pramanik 1982;Mane et al 2007;Rajalakshmi et al 2013;Narayanan et al 2013;Jana et al 2009;Rath et al 2011). These days, Bi 2 S 3 has received considerable attention as an absorber in photovoltaic applications (Kamat 2008).…”
Section: Introductionmentioning
confidence: 99%